LAPORAN KASUS: ANALISIS KOMBINASI PENGGUNAAN HEPATOPROTEKTOR PADA CEDERA HATI KARENA INFEKSI BAKTERI STREPTOCOCCUS VIRIDANS - Muhammad Hasan Andryanto; Fauna Herawati; Umi Fatmawati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Streptococcus viridans is one of the bacteria that can cause Community-Acquired Pneumonia (CAP). CAP disease has a higher prevalence of non-alcohol-related fatty liver disease (NAFLD). Continuous increase in fat levels in the liver triggered by pneumonia can cause inflammation in the liver, it causes a rapid decline in liver function and results in increased levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and total bilirubin. The use of hepatoprotectors in conditions of impaired liver function is essential to improve liver cell regeneration and promote liver detoxification. One of the drugs and supplements that can act as a hepatoprotector is ursodeoxycholic acid (UDCA) and Curcuma. Here we report the use of hepatoprotector drugs in cases of Community-Acquired Pneumonia (CAP) disease due to Streptococcus viridans bacteria in patients without comorbidities with the results of liver function test examinations from the beginning of hospital admission, during treatment, until the patient is discharged. The purpose of our case report is to illustrate the effect of the combined use of UDCA and Curcuma drugs on liver injury due to Streptococcus viridans bacterial infection in order to prevent complications, morbidity, mortality and improve the quality of life of patients. Based on the case reports that we present, the combined use of UDCA and Curcuma drugs as hepatoprotectors can improve liver function with reduced parameters of AST, ALT, and total bilirubin levels.